(untitled) (International Journal of Business, Economics and Management, 2018)
Social entrepreneurship is the fastest growing field in the world. Social entrepreneurship is a fundamental kind of enterprise that helps to boost the society along with the economy of any nation. Social entrepreneurship is gaining attention in Pakistan as well; however, the development is still moderate. It has gotten a progressive modification in Pakistan up to some extent, in term of innovation in the market, enhancing the social investment or trade, creating job opportunities and alleviation of poverty. Social entrepreneurship is crucial to open the growth and economic inclusion, for rising economies such as Pakistan. Economy and social models of Pakistan demands to revamp it. Therefore, the aim of this study is to investigate that what are the essential confronts and difficulties faced by social entrepreneurship in the limits of Pakistan and how social entrepreneurship could add in building up the economy of Pakistan?. Social business enterprise is a part of the social economy whereas social economy is a part of economic realism.